2019
DOI: 10.1111/jicd.12399
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a non‐fluoridated microcrystalline hydroxyapatite dentifrice on enamel caries progression in highly caries‐susceptible orthodontic patients: A randomized, controlled 6‐month trial

Abstract: Aim The aim of the present randomized, controlled trial was to compare the impact of the regular use of a fluoride‐free microcrystalline hydroxyapatite (HAP) dentifrice and a 1400 ppm fluoride control dentifrice on caries progression in 150 highly caries‐active orthodontic patients. Methods The primary outcome was the occurrence of lesions with International Caries Detection and Assessment System (ICDAS) ≥code 1 on the vestibular surfaces of teeth 15‐25 within 168 days after fixation of orthodontic brackets. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(115 citation statements)
references
References 20 publications
8
101
0
1
Order By: Relevance
“…[15]). Among these calcium-based cariespreventive agents, casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) has been studied intensively [7,9,10,16], while recently several studies have been published investigating synthetic particulate HAP (Ca 5 (PO 4 ) 3 (OH)) as another calcium phosphate-based compound [17][18][19][20]. HAP has often been proposed as a biomimetic agent for directly filling up micropores on demineralized tooth surfaces [17] and by reducing initial bacterial colonization on enamel surfaces [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15]). Among these calcium-based cariespreventive agents, casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) has been studied intensively [7,9,10,16], while recently several studies have been published investigating synthetic particulate HAP (Ca 5 (PO 4 ) 3 (OH)) as another calcium phosphate-based compound [17][18][19][20]. HAP has often been proposed as a biomimetic agent for directly filling up micropores on demineralized tooth surfaces [17] and by reducing initial bacterial colonization on enamel surfaces [18].…”
Section: Introductionmentioning
confidence: 99%
“…HAP has often been proposed as a biomimetic agent for directly filling up micropores on demineralized tooth surfaces [17] and by reducing initial bacterial colonization on enamel surfaces [18]. However, in patients exhibiting high plaque scores the primary mode of action of HAP as an oral care agent may be to act as a calcium phosphate reservoir when deposited in oral biofilms, potentially releasing Ca 2+ and (hydrogen) phosphate ions H 2 PO 4 − , HPO 4 2− and PO 4 3− upon bacterial acid challenge and thus maintaining a state of higher saturation with respect to these ions at the tooth surface [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…13 HAP particles interact with enamel surfaces as shown in vitro, 14 in situ, 15 and in vivo. 16,17 Clinical studies have shown effects of HAP-based toothpastes, for example, in prevention of enamel caries 17 and reducing dentin hypersensitivity, 18 as well as in improving periodontal health. 19 Additionally, HAP particles reduce bacterial colonization to enamel surfaces in situ similar to chlorhexidine without having antibacterial effects, but showing antiadherent properties.…”
Section: Introductionmentioning
confidence: 99%
“…Principal dermatological features found in 200 patients included: xerosis, acne, alopecia, caries, hypertrichosis, and Russell's sign in bulimia nervosa and xerosis and hypertrichosis, acne, alopecia, and caries in AN. 30 As for children and adolescents, Schulze et al 32 observed xerosis of the skin, diffuse hypertrichosis, acrocyanosis, scars, diffuse effluvium, artifacts, brittle nails, and onychophagia. Significant association was found between the presence of hypertrichosis and the existence of amenorrhea or a body mass index of less than 16 kg/m 2 .…”
Section: Study Of Dermatological Statusmentioning
confidence: 99%
“…They do not show potential risks associated with fluorides, but can facilitate erosion/caries control. 30…”
Section: Study Of Oral Manifestationsmentioning
confidence: 99%